2022
DOI: 10.1002/smll.202201410
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Oxygen Evolution Reaction on Polyethylene Glycol‐Modified BiVO4 Photoanode by Speeding up Proton Transfer

Abstract: The rate‐determining step of the oxygen evolution reaction based on a semiconductor photoanode is the formation of the OO bond. Herein, polyethylene glycol (PEG)‐modified BiVO4 photoanodes are reported, in which protons can be transferred quickly due to the high proton conductivity of PEG, resulting in the acceleration of the OO bond formation rate. These are fully demonstrated by different kinetic isotope effect values. Moreover, the open‐circuit voltage (Uoc) further illustrates that PEG passivates the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…23b that the KIE values of BVO are all higher than 2, indicating that the proton transfer process is the RDS of the water oxidation reaction, corresponding to the O—H bond rupture 17 . The KIE values of PTh/BVO are less than that of BVO, which means that the proton transfer process is well promoted, thus the water oxidation reaction kinetics can be improved more effectively and holes can be fast transferred to the water 57 , 58 . This can be elucidated by the good hydrophilicity of PTh (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23b that the KIE values of BVO are all higher than 2, indicating that the proton transfer process is the RDS of the water oxidation reaction, corresponding to the O—H bond rupture 17 . The KIE values of PTh/BVO are less than that of BVO, which means that the proton transfer process is well promoted, thus the water oxidation reaction kinetics can be improved more effectively and holes can be fast transferred to the water 57 , 58 . This can be elucidated by the good hydrophilicity of PTh (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All samples immediately exhibit a significant photocurrent intensities upon intermittent irradiation with a 300 W Xe lamp (Figure d). Besides, SiW 12 -CTF (4.12 uA/cm 2 ) exhibits the highest photocurrent intensities in compounds 1 – 3 , and reaches 1.5 times higher photocurrent density compared to bare CTF (2.48 uA/cm 2 ). , Subsequently, electrochemical impedance spectroscopy (EIS) tests were employed to value the interfacial resistance and charge transfer efficiency . In general, the smaller the radius of the semicircular Nyquist plot, the lower the interfacial migration resistance.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Subsequently, electrochemical impedance spectroscopy (EIS) tests were employed to value the interfacial resistance and charge transfer efficiency. 41 In general, the smaller the radius of the semicircular Nyquist plot, the lower the interfacial migration resistance. As expected, POM-CTFs exhibit smaller arc radius than the pure CTF, especially SiW 12 -CTF with the smallest arc radius, which demonstrates that grafting POMs onto CTF could improve photocatalytic activity (Figure 3e).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Moreover, this suggested that the attachment of the FeCo-MOF onto the surface of Fe 2 O 3 effectively passivated the surface states and suppressed charge recombination. Deng et al [123] achieved surface passivation of BiVO 4 photoanodes by simply immersing them in a polyethylene glycol (PEG) solution. Open-circuit voltage measurements showed that treated BiVO 4 exhibited a higher potential difference, indicating that the anchored PEG functioned as a passivating agent for surface states, preventing charge recombination.…”
Section: Surface Passivationmentioning
confidence: 99%